2021
DOI: 10.1371/journal.pone.0257769
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting uptake of the levonorgestrel-releasing intrauterine device: A mixed-method study of social franchise clients in Nigeria

Abstract: Background Despite the positive characteristics of the levonorgestrel-releasing intrauterine device (IUD)–a long-acting, highly effective contraceptive with important non-contraceptive attributes–the method has not been widely available in low- and middle-income countries. This study of hormonal IUD, copper IUD, implant and injectable users in Nigeria compares their characteristics, reasons for method choice, and experiences obtaining their method. Methods We conducted a phone survey with 888 women who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Satisfaction with the hormonal IUD was generally high with 80%-98% reporting being satisfied or very satisfied with method use across the time points when data were collected. [20][21][22][23][24] The study in Nigeria and Zambia that included copper IUD and implant users also documented high satisfaction rates with other LARCs (100% in Nigeria and 98% in Zambia for the 21 Brunie et al 22 Brunie et al 23 Brunie et al Cumulative continuation rates for the hormonal IUD were consistently high, ranging from 81%-95% at 12 months.…”
Section: Satisfaction Rates and Perceived Positive Methods Attributesmentioning
confidence: 89%
See 3 more Smart Citations
“…Satisfaction with the hormonal IUD was generally high with 80%-98% reporting being satisfied or very satisfied with method use across the time points when data were collected. [20][21][22][23][24] The study in Nigeria and Zambia that included copper IUD and implant users also documented high satisfaction rates with other LARCs (100% in Nigeria and 98% in Zambia for the 21 Brunie et al 22 Brunie et al 23 Brunie et al Cumulative continuation rates for the hormonal IUD were consistently high, ranging from 81%-95% at 12 months.…”
Section: Satisfaction Rates and Perceived Positive Methods Attributesmentioning
confidence: 89%
“…Among those who were prior contraceptive users, the majority in most studies reported using a short-acting method as their last method before uptake of the hormonal IUD (data not shown). [20][21][22][23][24] Continuation Rates…”
Section: Previous Methods Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the popularity of injectables in Zambia, we also included injectable users to support a broader exploration of differences between women choosing various methods. With the exception of another study conducted in Nigeria [ 21 ], this is, to our knowledge, a rare side-to-side examination of users of these four methods in real-world conditions. Specific objectives were to describe women choosing the hormonal IUD and women choosing other methods in terms of their characteristics, reasons for method choice, and experiences getting their method.…”
Section: Introductionmentioning
confidence: 93%